Genome-wide meta-analysis identifies five new susceptibility loci for cutaneous malignant melanoma - Law, M.; Bishop, D.; Lee, J.; Brossard, M.; Martin, N.; Moses, Eric; Song, F.; Barrett, J.; Kumar, R.; Easton, D.; Pharoah, P.; Swerdlow, A.; et al. (2015)
Thirteen common susceptibility loci have been reproducibly associated with cutaneous malignant melanoma (CMM). We report the results of an international 2-stage meta-analysis of CMM genome-wide association studies (GWAS). This meta-analysis combines 11 GWAS (5 previously unpublished) and a further three stage 2 data sets, totaling 15,990 CMM cases and 26,409 controls. Five loci not previously associated with CMM risk reached genome-wide significance (P < 5 × 10−8), as did 2 previously reported but unreplicated loci and all 13 established loci. Newly associated SNPs fall within putative melanocyte regulatory elements, and bioinformatic and expression quantitative trait locus (eQTL) data highlight candidate genes in the associated regions, including one involved in telomere biology.